Managerial Overconfidence and Debt Decision: Evidence from Malaysia - Irene, Wei Kiong Ting; Noor Azlinna, Azizan (Academic Research Online Publisher, 2015)
This paper investigates the impact of managerial overconfidence and firm’s debt decision. Dynamic panel models are employed to examine the relationship between managerial overconfidence and debt decision of publicly listed companies in Malaysia for the period of 2002-2011. The objective of this study is to investigate the relationship between managerial overconfidence and firm debt decisions from three perspectives based on MARS model. The findings are as follows. (1) When CEOs are motivated, their overconfidence is significantly and positively related to debt; (2) CEOs’ ability is significantly and positively related to debt; (3) Younger CEOs are taking more risk than older CEOs in Malaysian firm. (4) CEO who implement dual leadership structure tends to choose less debt; (5) Female CEOs are more confident and prefer more debt in Malaysian firms; (6) Firm debt is lower when CEO is also the founder. This study adds to the literature on behavioural finance by examining managerial over confidence and its impact to debt decision. The study also makes the methodology contribution by employing dynamic panel model to test the effect of managerial overconfidence and corporate debt decision